Analysis of the Arequipa, southern Peru, earthquake of 23 June 2001 by using GNSS data - Pirti, Atinc; Eren, Mehmet (INST GEOLOGY & GEOGRAPHY, 2025)
Peru is located above the damaging Peru-Chile Trench, which is the line where the Nazca Plate is subducting under the South American Plate. The two plates are approaching one another at a velocity of around 78 millimetres each year. There is a history of really big earthquakes in southwest Peru. The Arequipa, southern Peru, earthquake of 23 June 2001 had a moment magnitude of 8.4, a maximum Mercalli severity of VIII (severe), and occurred at 20:33:15 UTC (15:33:15 local time). It was the worst earthquake to ever strike the world since the 1965 Rat Islands earthquake and the most destructive earthquake to strike Peru since the disastrous Ancash earthquake of 1970. In this study, the horizontal and vertical displacements before and after the Arequipa, southern Peru, earthquake were analysed (kinematic GNSS results were compared with static GNSS results). As a result of these GNSS investigations (pre-motion on 20-21 June 2001), the obtained GNSS data for the precursor of the Arequipa earthquake were used. The AREQ IGS station before the earthquake, the movement in the horizontal components that occurred on 20-21 June 2001, and the decrease of this movement on 22 June 2001 seem to be a harbinger of the earthquake. In addition, the effects of the earthquake that occurred on 23 June 2001 were continued with aftershocks on 24 June 2001. In addition, this study may serve as a basis for understanding potential precursory patterns in this region.
Keywords: earthquake; Arequipa; Kinematic-Static GNSS; motion; precursor; SUBDUCTION; SIZE; Geology